Bentuk Penyajian Tari Cecah Inai Dalam Pesta Perkawinan Di Kecamatan Rengat Kabupaten Indragiri Hulu Provinsi Riau - Roni Apriyanto; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This study aims to describe and express the form of presentation of the Cecah Inai dance in a marriage party in Rengat District, Indragiri Hulu Regency, Riau Province. This research is a qualitative research with descriptive analytical methods. The object of the research is the Cecah Inai Dance in Rengat District, Indragiri Hulu Regency, Riau Province, which was focused on the form of presentation. Data collection techniques were done through literature review observations, interviews and documentation. The data were analyzedby using triangulation techniques which compare observational data and interview data as well as documentation data.The results of the study generally showed that the Cecah Inai Dance was performed in pairs, which could be displayed on the proscenium stage and an open area. It lasted for five minutes. The form of presentation of the Cecah Inai Dance at a wedding in Rengat Subdistrict, Indragiri Hulu District, Riau Province is in the form of pure representation. The elements of this dance presentation form are as follows: (1) Opening and closing greetings, Picking Motion, Grinding Motion, Splitting Motion, and Sowing or Spreading Motion. (2) The floor pattern of Cecah Inai Dance uses a pattern of straight lines or horizontal lines. (3) The accompanying music of Cecah Inai Dance consists of: accordion, gebane, and gong or mp3 recorded music.(4) The makeup used is beautiful and dashing makeup. The Dancers wear the BelangeTelok and Songket clothes as well as Peji or Tanjak for male dancers while female dancers wear Baju Kurung and Songket clothes and head accessories such as bun. (5) In addition, the Cecah Inai dance uses some properties such as turmeric rice, nail polish, fresh flour, and trays which are danced from the beginning to the end of the dance.